Geowissenschaften und Naturschutz in Schweden - Rückblick und Entwicklungstendezen - Soyez, Dietrich (ERDKUNDE, 1973)
Geologists and geographers were, from the start, involved in the Swedish conservation movement. Nevertheless, the number of geoscientific contributions - and also their influence in the selection of protected areas - was insignificant untal about 1960. The conservation value of the geoscientifically motivated designations in the last decade is doubtful in several ways, since representative sites have rarely been selected; instead it has been more common to choose unusual sites for protection. An increase in activities related to nature conservation can be recognised with the inventories of glacial gravels, and especially as a result of important government reports (after 1962). Since then, increasingly systematic geomorphological inventories have been carried out. These allow representative groups of forms and typical landscape types to be designated. Frequent attempts are being made to evaluate landscapes and individual sites, with the aim of allowing optimal choice of conservation areas from a variety of aspects. A short discussion of the situation in Germany completes the paper.